Immobilization of penicillin G acylase on amino functionalized mesoporous silica - Sridevi, N.; Pallavi, Shah; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
Penicillin G acylase was immobilized on Amino functionalized mesoporous silica by adsorption method. In this paper we present the effect of penicillin G acylase immobilization on amino-functionalized mesoporous silica and the effect of silica as host matrix on enzyme kinetics. The loading capacity of immobilized Penicillin G acylase is 34 mg protein per 0.5 g of SBA-15. About 65% of the protein was adsorbed on mesoporous silica. The stability of penicillin acylase was enhanced after immobilization on mesoporous silica. The adsorbed enzyme is more stable than the soluble form, both to temperature and pH environments and retained 73% of its activity.
Keywords: Amino functionalized mesoporous silica; Immobilization; Penicillin G acylase; pH and temperature stabilities